FUNGSI DAN NILAI DALAM CERITA RAKYAT BENDE DAN POKAE PADA ETNIK TOLAKI MEKONGGA (Function and Value Contained in Bende and Pokae Folklores in Tolaki Mekongga Ethnic ) - Ustianti Ustianti; Darwan Sari (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2021)
Folklore is an important source of regional cultural information as well as a cultural archive storing various data and information on regional culture. This study aims to analyze and to describe the functions and values ​​contained in the folklore of Tolaki Mekongga ethnic group in Wundulako District. This study uses a qualitative method. This research was conducted in Wundulako District, Kolaka Regency. Data collection was carried out through in-depth interviews, and document and literature study. The data analysis is carried out by transcription and translation procedures or stages, followed by heuristic and hermeneutic reading, and then ended by identifying the part (variant) of the story having a socio-cultural function and a variant of the story containing cultural values ​​with appropriate interpretation. Based on the results of the research, in the folklore Bende (Benteng) and Pokae (the name of the spring) there are social functions and cultural values. The social functions contained in these stories are: as a media for delivering information, as a means of preserving the language / dialect of the Mekongga area, as a means of preserving Tolaki Mekongga culture, as a means of legitimizing power, and as a source of local history. Meanwhile, these cultural values ​​consist of three values: religious, social, and moral values.